The perception of belonging: Latino undergraduate students participation in the social and academic life at a predominantly white private university - Valdés Ingelmo, José Joaquin, Jr., author; De Miranda, Michael A., advisor; Chavez, Ernest L., committee member; Jennings, Louise B., committee member; Timpson, William M., committee member (Colorado State University. Libraries, 2012)
This study explores the perception of belonging by Latino undergraduate students attending a predominantly White private university by documenting, in their "own voices," the extent of their participation in the social and academic life of the campus. Tinto (1975) suggests that, the process of dropout from college can be viewed as a longitudinal process of interaction between the individual and the academic and social systems of the college during which a person's experiences in those systems (as measured by his/her normative and structural integration) continually modify his goal and institutional commitments in ways which lead to persistence and/or to varying forms of dropout. (p. 94). In addition, other researchers have added to the growing body of literature on students' perceptions of the college environment. Hurtado and Carter (1997) suggest that, "Studying" a sense of belonging allows researchers to assess which forms of social interaction (academic and social) further enhance students' affiliation and identify with the colleges" (p. 328). In addition, Hurtado and Carter stated that, "understanding students' sense of belonging may be the key to understanding how particular forms of social and academic experiences affect these (racial and ethnic minority) students" (p. 324). They also asserted that, "further research is necessary to understand racial and ethnic minority students' views of their participation in college as an important part of the process of engagement in the diverse learning communities of a college" (p. 324). In addition, studies by Allen (1988), Oliver, Rodriguez and Mickelson (1985) and Smith (1988) have indicated that in predominantly White campuses underrepresented students are alienated from the mainstream of campus life. The research approach for this study utilized a phenomenological form of qualitative inquiry. This approach seeks to understand the central underlying meaning or essence of an individual's experience. Themes related to the Latino's students perceptions of socially and academically belonging emerged from the interview data. It is my desire that the emerging insights will serve to help higher education professionals create a welcoming and supportive campus climate for Latino undergraduate students. I believe that a supportive campus climate will result in an increase in the Latino graduation rate. Further, I undertook this inquiry, "not so much to achieve closure in the form of definitive answers to the problems but rather to generate questions that raise fresh, often critical awareness and understanding of the problems" (Schram, 2003, p. 4).
Keywords: retention; Latinos; student success; campus culture; inclusion